Fabrication of poly(pyrrole-3-carboxylic acid)/graphene oxide composite thin film for glucose biosensor. (2019) - Thunyakontirakun, Wachirawit; Sriwichai, Saengrawee; Phanichphant, Sukon; Janmanee, Rapiphun
Abstract: An electrochemical glucose biosensor based on poly(pyrrole-3-carboxylic acid)/graphene oxide (PP3C/GO) composite thin film was developed by immobilizing glucose oxidase (GOx) onto the surface of composite thin film via covalent linkages. The PP3C/GO composite thin film was fabricated on indium tin oxide (ITO) coated glass substrate by electrochemical polymerization. The glucose biosensor was constructed with immobilization of GOx on PP3C/GO composite thin film by covalent attachment. The developed glucose biosensor was characterized by cyclic voltammetry, scanning electron microscopy (SEM), electrochemical impedance spectroscopy (EIS) and amperometry. It was found that the presented functionalized polypyrrole/graphene oxide composite thin film showed good electroactivity in neutral PBS solution and could be applied to the detection of biomolecule. The presented biosensor exhibited a high sensitivity and selectivity for the detection of glucose with a wide detection linear range from 1 to 20 mM, correlation coefficient of r 2 = 0.9957, response time ∼5 s, and low detection limit (S/N = 3) of 0.05 mM. It also exhibited high stability and specificity to glucose. Therefore, it can be concluded that an electrochemically fabricated PP3C/GO composite thin film is a promising candidate as smart material for amperometric glucose biosensor.